Regional and international positions of the Azerbaijani - Armenian conflict on the Karabakh region (Journal of the College of Basic Education, 2023)
This research aims to take a look at the most important regional and international situations that contributed to the freezing and ignition of the Azerbaijani-Armenian conflict, in which many parties, including international and regional, intervened .in order to clarify all of the above, a descriptive and analytical approach was adopted to take a comprehensive look at the active parties to the conflict. the most important results reached are that regional and international countries did not contribute to achieving peace in the region, but each party contributed to fueling the conflict in proportion to its goals and interests in the region.